Study Of Hospital Noise At Parit Buntar Hospital, Parit Buntar, Perak. - Zulharis, Muhammad Haris (Universiti Sains Malaysia, 2019)
This study focuses on monitoring hospital noise in the study areas of Parit Buntar Hospital. The objectives of this study were to measure noise levels of indoor and outdoor of the hospital, to identify the source of indoor and outdoor noise and to produce the outdoor noise profile at the hospital. This study was conducted within two days representing holiday (Thaipusam Festival) which is Monday for outdoor areas and weekday which is Tuesday for indoor areas to measure the noise environment by using a sound level meter. The noise measurement was collected in every 3 minutes with interval 1 second. The noise levels measurement were monitored in the morning (0800-1030), afternoon (1200-1430), evening (1600-1830) and night (2030-2300). The list of noise sources was recorded manually from the observation together with time occurrence and speed gun for measuring traffic speed of various type of vehicle on roads. Minimum noise level (Lmin), maximum noise level (Lmax), noise level exceed 10% (L10), 50% (L50) and 90% (L90) were measured to assist in assessing the existing noise level at a various pre-determined location. Results showed that the monitored noise levels in term of average LAeq (mean) between 53.9 dB(A) to 56.1 dB(A) for outdoor due to traffic flow, the number of vehicles influenced the reading of the noise to the surrounding and generator from Mydin Mall while for indoor average LAeq (mean) between 51.8 dB(A) to 61.9 dB(A) for Ward Angerik, Ward Dahlia, Ward Mawar and Ward Melor due to staff conversation, phone ringing, cough, scrap chair, radio, audio and ceiling fan also contributed noise to the surrounding. About 90% and above the noise levels recorded were exceeded the Maximum Permissible Sound Level by Receiving Land Use for Planning and New Development by Department of Environmental (DOE) which is 50 dB(A) in the day time and 40 dB(A) in the night time.